EFEKTIVITAS LAYANAN INFORMASI DALAM MENCEGAH AGRESIVITAS SISWA - Takdir Nehe (Counseling For All : Jurnal Bimbingan dan Konseling, 2023)
This research was motivated by variations in student behavior accompanied by aggressiveness, as well as the not yet optimal role of Guidance and Counseling teachers in providing information services to students at BNKP Telukdalam Christian Private Middle School. This research aims to; 1) describe the level of student aggressiveness before being provided with information services; 2) describe the level of student aggressiveness after being provided with information services; and 3) test the effectiveness of information services in preventing student aggressiveness. This research uses a quantitative approach with the Pre-Experimental Design method, namely the one group pretest-posttest design. The population in this study were class IX students of the BNKP Telukdalam Christian Private Middle School. The research sample was selected using a purposive sampling technique of 35 people. The research results showed that, 1) the level of student aggressiveness before providing information services was in the high category with an average score of 103.2 with a percentage of 68.8%; 2) the level of student aggressiveness after providing information services is in the low category with an average score of 75.14 with a percentage of 50.1%; and 3) based on the calculation results, Zcount = 5.16, N= 35 and α = 0.05. (5.16 > 0.05) means that H0 is rejected and Ha is accepted, thus it can be stated that the information service is effective in preventing the aggressiveness of class IX students at BNKP Telukdalam Christian Private Middle School. Suggestions: 1) students are expected to be proactive in every information service activity; 2) for guidance and counseling teachers to carry out periodic needs assessments and analysis, optimize the provision of information services by utilizing media and using relevant methods; and 3) to school principals and teachers to fully support the BK service activity program.